?EFFICACY OF FISH SILAGE AND FISH MEAL ON THE GROWTH PERFORMANCE OF NILE TILAPIA, OREOCHROMIS NILOTICUS FRY - HOQ, M.E.; BHUIYAN, A.K.M.A.; BEGUM, M.; ZAHER, M. (Biological Sciences - PJSIR, 1995)
A 50-days feeding trial using Oreochromis niloticus fry was conducted to evaluate the performance of fish silage and fish meal prepared from marine trash fish. The fry were maintained on 3 diets, fish silage and fish meal (prepared fromsame raw materials)andcommercialgrade fishmealas major dietary protein source at 30% level.On the basis of observed growth rate, food conversion ratio, protein efficiency ratio and net protein utilization, the diet containing fish silage produced the best growth performance.There was no significant difference (P>O.05)between diet containing fish silage and laboratory grade fish meal but these were significantly different from commercial grade fish meal diet.